The Need to Avoid a Second Victim - Alves Iulianello, Annunziata (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2020)
Traditionally in penal doctrine, victims swapped roles: main character and supporting roles, taking up in penal procedure the role of mere spokesperson. With modern victimology, the need for a more important role on the part of the victim appeared. Secondary victimism —taken by formal instances of social control— is directly connected with an increase in black figures. In this study we will lead a succinct analysis of the importance of avoiding a second victim.
Keywords: victim; penal procedure; victimology; black figures; second victim